2013
DOI: 10.1111/iju.12207
|View full text |Cite
|
Sign up to set email alerts
|

Acute bacterial prostatitis after transrectal ultrasound‐guided prostate biopsy: Epidemiological, bacteria and treatment patterns from a 4‐year prospective study

Abstract: Abbreviations & AcronymsObjectives: To evaluate the incidence, and clinical and bacterial features of iatrogenic prostatitis within 1 month after transrectal ultrasound-guided biopsy for detection of prostate cancer. Methods: From January 2006 to December 2009, 3000 patients underwent a 21-core transrectal ultrasound-guided prostate biopsy at Henri Mondor Hospital (Créteil, France) and were prospectively followed. All patients had a fluoroquinolone antimicrobial prophylaxis for 7 days. The primary study end-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
0
34
1
Order By: Relevance
“…First, the bacterial-infection model is not representative of all types of human prostatitis, because many patients with chronic prostatitis and chronic pelvic pain syndrome have no evidence of urinary tract infection (43). In addition, E. coli is not the only source for bacterial infection (39,44,45). Second, transurethral instillation of uropathogenic bacteria usually causes an immediate phase of acute inflammation followed a few months later by a second phase of multifocal chronic inflammation (34).…”
Section: Discussionmentioning
confidence: 99%
“…First, the bacterial-infection model is not representative of all types of human prostatitis, because many patients with chronic prostatitis and chronic pelvic pain syndrome have no evidence of urinary tract infection (43). In addition, E. coli is not the only source for bacterial infection (39,44,45). Second, transurethral instillation of uropathogenic bacteria usually causes an immediate phase of acute inflammation followed a few months later by a second phase of multifocal chronic inflammation (34).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical pattern and microbiological characteristics of ABP in patients with prior manipulation of the lower urinary tract has been reported to be different from that of ABP in patients without prior manipulation [2]. TRUS-TRBx is generally accepted as the standard procedure for diagnosing PCa, and direct bacterial seeding from a prostate biopsy is another common cause of ABP [3,7]. Although the incidence of TRUS-TRBx-induced acute prostatitis is low, it is a typically serious complication when it does occur.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, quinolone is still an effective antibiotic prophylaxis for Bx-ABP [3,16]. In a review of a large number of patients who underwent TRBx, on the basis of low incidence of Bx-ABP, the authors concluded that a quinolone-based regimen still represents an appropriate prophylaxis protocol to minimize the risk of Bx-ABP [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No resistance to imipenem was reported. 1 The authors raised an important question, "Is fluoroquinolone still an appropriate antibiotic prophylaxis for prostate biopsy?" On the basis of low incidence of infectious complications after biopsy, they concluded that the choice of fluoroquinolone is appropriate with regards to local bacteriological epidemiology; they explained that modifying the prophylaxis for a larger spectrum antibiotic could raise the resistance profile of the incriminating bacteria and subsequently cause more severe prostatitis.…”
mentioning
confidence: 99%